AUDIT KEMANAN INFORMASI MENGGUNAKAN ISO 27002 PADA DATA CENTER PT.GIGIPATRA MULTIMEDIA - Afandi, Herman; Darmawan, Abdi (244-5567)
PT. Giga Patra Multimedia Company is a private company which concentrates on Internet service providers, hosting sales and procurement of supplies and support equipment technology. Given the importance of enterprise information, then the information must be protected or secured by theentire personnel of the company. All information company that there must have backup and recovery baik. Sementara that goes with it, as long as the company PT.Giga Multimedia Patra stands have been some problems, among others, are often found to leak information and hackingwebsites terhadapa customers arriving at the web server. In addition, it is feared may propagate in the abuse informasi. Maka in perlukanya internal audit in the company PT.Giga Patra Multimedia. Types of audits are used in this research that uses an internal audit of security standards Iso27002: 2013. And some clauses yitu Security Human Resources (Clause 7), Access Control (Clause 9), elderly physic Safety and Environment (Clause 11), Management Communication and Oprasi 12) .With the security audit information on PT. Giga Multimedia Patra can find out the weaknesses of the system is the cause of information security problems which have occurred. Besides this audit can measure the level of security by PT. Giga Patra Multimedia. From the results of a security audit of information systems that have been done, it was concluded that in the field of HumanResource Security (Clause 7) yielded values 2.71 and maturity level in the field of Access Control (Clause 9) has a value of 2.75 and a maturity level and field of Physical Security Environment (Clause 11) security resources Manuia generate value maturity level of 2.75 is located on level 2(limited / repeatable) which means that security controls are under development, there have been limited documentation but no training and measuring the effectiveness of security controls, and field operational ( Clause 12) yielded values of 1.33 maturity level that is at the level of Level 2 (limited / repeatable) At this level, security controls are still in development and / or there is limited documentation to support the need. Expected PT. GIGA PATRA MULTIMEDIA can do the repair information system security management, rules, and procedures that the information system security threats related to information security can be minimized.Keywords : Audit, ISO 27002, audit kemanan data center,kemanan informasi